Implementation of Cluster Analysis on Districts/Cities in Banten Province Based on Factors Causing Stunting in Toddlers - Mahuda, Isnaini; Rofiroh, Rofiroh; Fitriani, Meida (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2025)
Indonesia is a country in Southeast Asia that has the fifth highest prevalence of stunting in world and as a country that has a relatively high stunting rate. Banten Province, as one of provinces in Indonesia, is in the bottom five provinces with the worst stunting cases according to results of Indonesian Toddler Nutrition Status Survey (SSGBI) 2021. Many efforts have been made to resolve this stunting problem. The condition of stunting is usually characterized by the toddler's length or height being less than the normal toddlers of the same age. Several factors causing stunting can be identified so that the government can take appropriate steps to reduce stunting rates in Indonesia, especially in Banten province. Banten province consists of several districts/cities which have their own characteristics, so it is necessary to analyze the grouping of factors causing stunting based on districts/cities in Banten province using hierarchy cluster analysis. The cluster analysis method used in this research was Single Linkage method with Euclidian distance. The results of this research showed that two clusters were obtained based on the grouping results, where first cluster had a higher average percentage of babies born alive with Low Birth Weight (LBW) and percentage of average per capita monthly expenditure for food compared to second cluster. In other hand, percentage of households with access to adequate sanitation and drinking water in first cluster had smaller average value than second cluster.